(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
Ukraine’s financial reporting framework prioritizes regulatory compliance but fails to meet management information needs. This study reveals systemic limitations – information latency, data aggregation, and poor integration – through sectoral case analysis. Findings demonstrate how current practices constrain decision-making and propose unified reporting systems to balance transparency with operational utility.